Modeling of Water Treatment Plant using Hybrid Petri Nets - Murdianto, Deny ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2022)
Hybrid Petri nets are modeling framework for a system that contains discrete and continuous states. In this paper, we construct a model of water treatment plant using Hybrid Petri nets. We choose hybrid petri nets because the water treatment plant contains discrete and continuous parts. The discrete part consists of the state of pumps and the continuous part consists of water volume in each processing unit. The Petri Nets obtained were further simplified to facilitate simulation. Through simulation we can determine the amount of water production with certain specifications.